Gastrointestinal parasites in wild and exotic animals from a zoo in the State of Bahia, Brazil - first record (Research, Society and Development, 2022)
Parasitic infections can be a serious health problem for wild animals kept in captivity, however, coproparasitological assessments in Brazilian zoos are scarce and spaced. Therefore, this study aimed to evaluate the occurrence of endoparasites in the feces of wild and exotic captive animals in the zoo of Matinha Municipal Park, Itapetinga, Bahia, Brazil, the only zoo in the interior of Bahia, through the Mini-FLOTAC® technique, providing subsidies for the diagnosis and therapeutic treatment of parasitized animals. From May to August 2022, 124 stool samples from 35 species of reptiles, birds and mammals were collected. Analyzes were performed using the Mini-FLOTAC® technique in combination with Fill-FLOTAC®. The results show that 70.97% of the samples were positive for at least one gastrointestinal parasite. Birds (76.7%; 33/43) were the most parasitized animals. Twenty-seven taxa of gastrointestinal parasites were identified, whether cysts, oocysts or eggs, being 8 protozoans and 19 helminths, with a predominance of coccidia, Oxyurideae and Angusticaecum sp. for reptiles, coccidia, Ascaridia spp., Heterakis spp. and Strongyloides spp. for birds, coccidia, Ancylostomatidae, Strongylida and Strongyloides spp. for mammals. In summary, the results presented reveal the importance of periodically carrying out coproparasitological examinations in zoos, in order to subsidize interventions by the technical team to promote the health and well-being of animals. This work constitutes the first publication on the coproparasitological evaluation of animals from a zoo in the state of Bahia.